2019
DOI: 10.1021/jacs.9b05550
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic and Structural Basis for Inhibition of Copper Trafficking by Platinum Anticancer Drugs

Abstract: Copper (Cu) is required for maturation of cuproenzymes, cell proliferation, and angiogenesis, and its transport entails highly specific protein−protein interactions. In humans, the Cu chaperone Atox1 mediates Cu(I) delivery to P-type ATPases Atp7a and Atp7b (the Menkes and Wilson disease proteins, respectively), which are responsible for Cu release to the secretory pathway and excess Cu efflux. Cu(I) handover is believed to occur through the formation of threecoordinate intermediates where the metal ion is sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…37 As shown in Figures 7a and S8, the addition of gradient concentrations of cisplatin and DPFP into the purified NDM-1 sample resulted in a gradual decrease in molar equivalents of Zn (II) to NDM-1, accompanied by the increase of Pt(II) and Pd(II) in the binding to NDM-1; eventually, 0.96 and 1.1 equiv of Zn(II) were displaced, whereas 1.15 and 1.02 To better understand the detail of the interaction between metal complexes and wild-type NDM-1, MALDI-TOF mass spectrometry was employed to characterize the binding of cisplatin and BPC to NDM-1. As shown in Figure 7b, after the addition of cisplatin into the NDM-1 sample for 2 h, we observed a complete mass shift peak of the protein complex with a MW of 25 096 Da, which was the sum of the MW of NDM-1 (24 930 Da) and one cisplatin with two NH 3 's (229 Da) binding to the Cys208 residue, which was similar to the binding mode of the heterodimeric complex Atox1−Cu(I)− Mnk1 by a platinum anticancer drug (cisplatin), 38 and the loss of one Zn(II) ion (65 Da) and of two protons. For the NDM-1−BPC complex, a shift peak of the protein complex with a MW of 24 977 Da was observed, which was the sum of the MW of NDM-1 (24 930 Da) and one palladium ion (106 Da) and the displacement of one Zn(II) ion (65 Da) and the loss of six protons (Figure S9), which suggested that the metal complexes strongly bound to NDM-1, therefore resulting in the loss of one zinc ion at the active site as evidenced by the above thermal shift assays.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…37 As shown in Figures 7a and S8, the addition of gradient concentrations of cisplatin and DPFP into the purified NDM-1 sample resulted in a gradual decrease in molar equivalents of Zn (II) to NDM-1, accompanied by the increase of Pt(II) and Pd(II) in the binding to NDM-1; eventually, 0.96 and 1.1 equiv of Zn(II) were displaced, whereas 1.15 and 1.02 To better understand the detail of the interaction between metal complexes and wild-type NDM-1, MALDI-TOF mass spectrometry was employed to characterize the binding of cisplatin and BPC to NDM-1. As shown in Figure 7b, after the addition of cisplatin into the NDM-1 sample for 2 h, we observed a complete mass shift peak of the protein complex with a MW of 25 096 Da, which was the sum of the MW of NDM-1 (24 930 Da) and one cisplatin with two NH 3 's (229 Da) binding to the Cys208 residue, which was similar to the binding mode of the heterodimeric complex Atox1−Cu(I)− Mnk1 by a platinum anticancer drug (cisplatin), 38 and the loss of one Zn(II) ion (65 Da) and of two protons. For the NDM-1−BPC complex, a shift peak of the protein complex with a MW of 24 977 Da was observed, which was the sum of the MW of NDM-1 (24 930 Da) and one palladium ion (106 Da) and the displacement of one Zn(II) ion (65 Da) and the loss of six protons (Figure S9), which suggested that the metal complexes strongly bound to NDM-1, therefore resulting in the loss of one zinc ion at the active site as evidenced by the above thermal shift assays.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Additionally, inside cells, Pt drugs interfere with the copper chaperones involved in the metal localization in the nucleus and cytosol as Atox1 system. Efflux regulation of Cu, occurs affecting P-type ATPases Atp7a and Atp7b also known as the Menkes and Wilson disease proteins, respectively [117,118]. Platinum center can bind tightly to sulphur atoms donor due to its softer nature than Cu(I) thus affecting copper homeostasis and consequently the activity of copper in angiogenic processes.…”
Section: Platinum Drugsmentioning
confidence: 99%
“…DNA is deeply hidden in the nucleus of the cancer cell, and many drugs targeting DNA must pass through a series of barriers, such as the cytoplasmic membrane, lysosome, and nuclear membrane before entering the nucleus, making a large problem for drug delivery. In fact, only about 1–4% of cisplatin entered the nucleus after cellular internalization and even less (0.4%) of DOX entered the nucleus ( Yu Cao et al, 2019 ; Lasorsa et al, 2019 ), which inevitably cause some serious side effects and poor prognosis.…”
Section: Introductionmentioning
confidence: 99%